Detection of Porcine Fat in Olive Oil Based Facial Mask Formulations Using Fourier Transform Infrared (FTIR) Spectroscopy - Wulandari, Leli; Dhuha, Nur Syamsi; Handayani, Gemy Nastity (Halal Science, 2026)
The authentication of lipid sources in cosmetic products is essential due to regulatory, ethical, and religious concerns, particularly regarding the potential presence of porcine-derived ingredients. This study aimed to evaluate the applicability of Fourier Transform Infrared (FTIR) spectroscopy combined with Principal Component Analysis (PCA) for differentiating lipid profiles in olive oil–based facial mask formulations. Reference lipids, including porcine fat and olive oil, as well as lipid extracts from five commercial cosmetic products, were analyzed using FTIR spectroscopy within the mid-infrared region (4000–650 cm⁻¹). Characteristic absorption bands corresponding to triglyceride structures were observed in all samples, while differences between lipid sources were primarily identified within the fingerprint region (1500–1000 cm⁻¹). PCA was applied to enhance spectral discrimination and revealed clear separation between porcine fat and olive oil along the principal components. Most cosmetic samples (HCN, LTL, NR, and QN) were positioned closer to the olive oil reference, whereas one sample (MDG) showed spectral proximity to porcine fat. However, these results reflect spectral similarity rather than definitive confirmation of lipid origin. The findings indicate that FTIR spectroscopy combined with chemometric analysis can provide a rapid and non-destructive approach for preliminary screening of lipid sources in cosmetic matrices. Nevertheless, due to the limited number of samples and the complexity of cosmetic formulations, further studies incorporating broader sample sets and confirmatory analytical methods are required to support its application in halal authentication and quality control.